Green Human Resource Management: A Case Of Malaysia - Azmi, Fadhlur Rahim; Musa, Haslinda; Shahbodin, F.; Hasan, Hazmilah; Fam, Soo Fen (IOSR Journals, 2018)
Green human resource management (GHRM) has become a key business strategy for the significant organizations where human resource departments play an active part in going green at the organizations. The main purpose of this study focused on training and development of Employee Knowledge, Employee Skill and Employee Attitude towards the implementation of Green Human Resource Management (GHRM). A total of 150 questionnaires were distributed via email to the organizations who implemented GHRM in Malaysia, but only 100 were returned. The results of the analysis indicated employee skills as the most significant factors for organization to implement GHRM. For the practicality of this study, GHRM is anticipated to be well implemented when the employee skills are emphasized